Genetic variation analysis of the genus Passiflora L. using RAPD markers - Fajardo, Diego; Angel, F.; Grum, M.; Tohme, Joseph M.; Lobo Arias, Mario; Roca, W.; Sánchez, I. (Springer, 1998)
Genetic analysis based on Random Amplified Polymorphic DNA (RAPD) was carried out on 52 accessions representing 14 species of the genus Passiflora L. using 50 random 10-mer primers. A dendrogram constructed using the Dice similarity coefficient and the UPGMA algorithm based on 626 reproducible polymorphic products ranging in size from 2.8 to 0.3 Kb revealed high levels of variation within and among species, and clustering of accessions according to species. Similarity coefficients ranged from 0.929 to 0.075 showing a diverse genepool in the genus. Large intraspecific variation was found in P. ligularis and P. adenopoda while P. edulis and P. maliformis exhibited a low level of intraspecific variation. The clusters based on RAPD markers correlate fairly well to the present classification scheme based on morphological description with two exceptions. The subgenus Passiflora was split into P. edulis and the rest of the members of the subgenus Passiflora separated by the subgenus Tacsonia; secondly the two species of the subgenus Decaloba, P. adenopoda and P. coriacea, were not clustered together on the dendrogram of genetic relationships.